Daughter of the deep eaudiobook - Riordan, Rick (Disney Hyperion, 2021)
New York Times #1 best-selling author Rick Riordan pays homage to Jules Verne in his exciting modern take on 20,000 Leagues Under the Sea. "If you have ever craved a story that will leave your heart racing, your lungs gasping from the numerous twists and turns, your soul heaving from the effort of now carrying an ensemble cast, you will find all that and more in these pages."— New York Times best-selling author Roshani Chokshi Ana Dakkar is a freshman at Harding-Pencroft Academy, a five-year high school that graduates the best marine scientists, naval warriors, navigators, and underwater explorers in the world. Ana's parents died while on a scientific expedition two years ago, and the only family's she's got left is her older brother, Dev, also a student at HP. Ana's freshman year culminates with the class's weekend trial at sea, the details of which have been kept secret. She only hopes she has what it'll take to succeed. All her worries are blown out of the water when, on the bus ride to the ship, Ana and her schoolmates witness a terrible tragedy that will change the trajectory of their lives. But wait, there's more. The professor accompanying them informs Ana that their rival school, Land Institute, and Harding-Pencroft have been fighting a cold war for a hundred and fifty years. Now that cold war has been turned up to a full broil, and the freshman are in danger of becoming fish food. In a race against deadly enemies, Ana will make amazing friends and astounding discoveries about her heritage as she puts her leadership skills to the test for the first time. Rick Riordan's trademark humor, fast-paced action, and wide cast of characters are on full display in this undersea adventure. Complete your middle grade action-adventure collection with these titles: Percy Jackson and the Olympians: The Lightning Thief by Rick Riordan Artemis Fowl by Eoin Colfer Rick Riordan Presents: Aru Shah and the End of Time by Roshani Chokshi Rick Riordan Presents : City of the Plague God by Sarwat Chadda